Characterization of StAR protein of Rhinella arenarum (Amphibia, Anura) - Czuchlej, Silvia Cristina (2020)
The steroidogenic acute regulatory (StAR) protein performs the delivery of cholesterol from the outer to inner mitochondrial membrane. This is considered the rate-limiting step of acute steroid production, widely studied in mammals. However, there are only few reports regarding the characterization and expression of StAR protein in non-mammalian vertebrates. In this study, StAR protein sequence of Rhinella arenarum has been characterized and deduced from interrenal and testis cDNA sequences. StAR encodes a 285 amino acid protein with a conserved domain containing putative lipid binding sites. In vitro incubations showed that expression of StAR mRNA in testis, determined by qPCR, and testosterone synthesis determined by radioimmunoassay were stimulated after treatment with hCG and 8Br-cAMP. However, StAR mRNA expression results obtained with hCG show a higher stimulation than those obtained with 8Br-cAMP, even though steroidogenic production is the same with both treatments.